Funding liquidity risk and the cross-section of stock returns - Tobias Adrian; Erkko Etula (Federal Reserve Bank of New York, 2010)
We derive equilibrium pricing implications from an intertemporal capital asset pricing model where the tightness of financial intermediaries' funding constraints enters the pricing kernel. We test the resulting factor model in the cross-section of stock returns. Our empirical results show that stocks that hedge against adverse shocks to funding liquidity earn lower average returns. The pricing performance of our three-factor model is surprisingly strong across specifications and test assets, including portfolios sorted by industry, size, book-to-market, momentum, and long-term reversal. Funding liquidity can thus account for well-known asset pricing anomalies.
Keywords: G1; G12; G21; 330; Cross-sectional asset pricing; funding liquidity risk; ICAPM